PELATIHAN PEMBUKUAN SEDERHANA PADA PELAKU UMKM DI DESA SALAKAN SULAWESI TENGAH - Alvi Angelica; Ika Wulandari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The aim of this community service activity is to increase the understanding and knowledge of MSME players regarding simple bookkeeping, which includes recording cash books, calculating profit/loss, and separating personal money from business money. The implementation of simple bookkeeping training is aimed at MSMEs, namely TRI AL FAEYZA and AKBAR LAUNDRY. This service was carried out for approximately 30 days at Salakan Banggai, Central Sulawesi Islands. The method used is training and counseling. The activity was carried out in August 2023. As a result of this service activity, MSMEs better understand and know the importance of keeping simple bookkeeping, which includes recording cash books, calculating profit/loss, and separating personal money from business money. As well as the risks that will occur if you do not implement simple bookkeeping